Pengaruh Rotasi Audit, Leverage, Ukuran Perusahaan Klien, Komite Audit dan Fee Audit terhadap Kualitas Audit - Devina Harys Mawarini; Ni Nyoman Alit Triani (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the influence of Audit Rotation, Leverage, Client Firm Size, Audit Committee, and Audit Fees on Audit Quality. The research employs a quantitative method with a sample consisting of 109 companies from the Consumer Non-Cyclicals, Properties & Real Estate, and Energy sectors listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023. Data analysis was conducted using logistic regression techniques with SPSS software version 25. The study found that the Audit Rotation variable has a negative effect on Audit Quality, the Client Firm Size variable has a positive effect on Audit Quality, while the variables Leverage, Audit Committee, and Audit Fees have no significant effect on Audit Quality.